Three New Flavonoid Glycosides from the Fruits of Luffa echinata Roxb.- a Hepatoprotective Plant - Alam, Tanveer; Harrasi, Ahmed Sulaeman Al; Ahmed, Bahar; Najam, Lubna; Khan, Shah Alam (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Phytochemical investigation of bioactive polar extracts of Luffa echinata Roxb. fruits led to the isolation and characterization of three new flavone glycosides viz., 3,5,7,3?,4?-pentahydroxyflavone-3-[-O-?-Dglucopyranosyl- 7-O-?-D-glucopyranoside (1),3,5,7-trihydroxy-(7?,8?- dioxo,9?,10?,-dihydro[a]cyclohex ?13?,(14?), ?11?(12)-12?,13?,-dimethyl)-flavone-7-[-O-?-D-galactopyranosyl-(1?2)]-O-?-D-glucopyranoside (2), and 5,7,8,4?- tetrahydroxy flavone-7-[-O-?-D-xylosyl-(1?2)]-O-?-D-glucopyranoside (3). The structures of the newly isolated compounds were elucidated on the basis of spectral data and chemical evidences.The isolated compounds are found to be new analogs of tricetin, quercetin and isoscutellarin. Dhaka Univ. J. Pharm. Sci. 15(2): 117-125, 2016 (December)